The Role of The Ministry of Communications and Information In Preventing The Spread of Hoaxes During The 2024 Election - Raihan Fadhilah Putra; Andriyanto Adhi Nugroho (Dinasti Research, 2024)
According to the Indonesian Constitution, general elections (Pemilu) must be held in order to transfer power from one administration to another. The public's perceptions are distorted as a result of the propagation of hoaxes during elections. In addition to undermining a nation's political stability, hoaxes can harm the standing of the candidates and political parties involved. They can also compromise the integrity of the democratic process. According to Presidential Regulation of the Republic of Indonesia Number 22 of 2023 concerning the Ministry of Communication and Information, the Ministry of Communication and Information is the body in Indonesia that oversees the regulation of information and communication on social media and online media. In this study, we will look at Article 3 of the Presidential Regulation of the Republic of Indonesia Number 22 of 2023, which relates to the Ministry of Communication and Information. According to this regulation, Kominfo is tasked with taking proactive measures to stop the propagation of false information ahead of the 2024 election. Normative approaches are used in this kind of research. The study's findings demonstrate that, in order to comply with Article 3 of the Presidential Regulation of the Republic of Indonesia Number 22 of 2023 concerning the Ministry of Communication and Information, the Ministry will likely employ three main strategies to address hoaxes that circulate during the 2024 election. These strategies include: (1) implementing digital literacy at all societal levels through the National Digital Literacy Movement (GNLD); (2) moderating, curating, and removing content that contains hoaxes; and (3) establishing an Election Monitoring Desk in coordination with the Republic of Indonesia Police and the Election Supervisory Body to conduct law enforcement against those who fabricate and disse.